Pre-Islamic Central Asia - Shakhnoza Iminova (Zien Journals, 2024)
This article analyzes the cultural, economic and political development of Central Asia in the pre-Islamic period. The role of ancient civilizations such as the Sogdians, Bactrians, Parthians and Kushans in the region and their role in strengthening the cultural and economic ties between the East and the West through trade routes considered. The influence of religious beliefs, including Zoroastrianism, Manichaeism, and Buddhism in the region, and their contribution to cultural heritage are analyzed. The introduction of Islam to Central Asia and its influence on religious, cultural and political life are also covered. The article emphasizes the importance of preserving the high cultural heritage of Central Asia in the pre-Islamic period
Keywords: Pre-Islamic period; Sogds; Bactria; Parthia